ТАЪЛИМ ЖАРАЁНИДА ПЕДАГОГИК ТЕХНОЛОГИЯЛАРДАН ФОЙДАЛАНИШНИНГ УСТУВОР ОМИЛЛАРИ - Одашева, Ф.М. (SCIENCE and SOCIETY, 2021)
The article discusses the pedagogical conditions for the organization of the educational process on the basis of pedagogical technologies, the priorities of the teacher, the tasks of the educational process based on the technological approach and the qualities that can be acquired by the student.
Keywords: Technology; pedagogical technology; innovation; educational innovations